Analysis Effect of Profitability Ratio, Leverage Ratio, Audit Committee and Public Accounting Firm Size on Audit Delay - Nurhafifah Amalina; Firda Amelia; Wien Alfatah (Indonesian Management and Accounting Research, 2018)
The main purpose of this research is to analyze profitability ratio, leverage ratio, audit committees and public accounting firm size against Audit Delay. The multiple linear regression is the most common form of linear regression analysis is used to explain the relationship between the effect of independent variables (profitability ratio, leverage ratio, audit committee and public accounting firm size) and dependent (audit delay).  The data samples were obtained from the LQ-45 Index of Corporations which are listed on the Indonesia Stock Exchange (BEI). The data consists of a three years period from 2015 to 2017.  After completing the analysis study, it shows that only audit committees has a significant influence on Audit Delay, while profitability ratio, leverage ratio and public accounting firm size have no effect on such. Keywords: Multiple Linear Regression Analysis, Audit Delay, Profitability, Leverage, Audit Committee, Public Accounting Firm Size